Water Filling Pro - Azhari, Aliff Aiman; Abdul Ghani, Muhamad Hafiz; Sharuddin, Muhammad Shahin; Samion, Norhafiza (Multidisciplinary Applied Research and Innovation, 2022)
Customers always want a fast service. However, restaurants always faced the challenge of providing fast service especially if there many customers during peak time. Using up-to-date and automated machines could help expedite workers pace to prepare meals ordered by customers. Thus, Water Filling Pro is created to improvised water filling function to make it more efficient. The aim of this project is to make the machine move automatically and more effective in time required to preparing a cup of water. There are three main parts that need attention which is cup machine, conveyor and water pump. For the result, this improvised system managed to create the machine and achieve the objective where the cup will drop on the conveyor and move until a sensor detect the cup and it will stop for a while to make the water pump fill the water and the cup will move again to the end of the conveyor which a nearby the worker. The best time we get are 22 seconds while the restaurant that ready to cooperate with us took around 45 seconds which prove that the machine are faster than the existing system . By this improvisation, the system has a good potential to be in the market and looking forward to add Bluetooth in this system since this project unable to add it in the system.